The determinants of small and family owned hotel room rates - Ante Mandić; Elza Jurun (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2018)
Purpose Research explores the price determinants of the small and family owned hotels, as a specific segment of the overall hotel industry. Design/methodology/approach Hedonic pricing model has been designed to analyse the impact of 19 price determinants on 140 small and family owned hotels in Croatia, leading destination in Southeastern /Mediterranean Europe. The choice of variables follows recent literature, while data have been obtained from an official catalogue of small hotel and family hotel association. Findings Findings suggest that (1) the highest impact on small hotel prices is generated by hotel core facilities and attributes (category, wellness facilities, inner pool, elevator, mini bar, internet connection); (2) location same as following variables (children day-care and pets allowed) does not have significant impact on small hotel prices. Additionally, research results demonstrate that there are differences, considering price determinants, between small and family hotels and regular size hotels. Research limitations/implications The main limitations of this study are reliance on catalogue data and mostly dummy variables. Despite those shortcomings, findings provide valid and encouraging starting point for any future analysis of differences between hotels market segments. Results are beneficial to researchers and practitioners especially those involved in the strategic planning process in the hotel industry Originality/value Despite they are a specific segment of the overall industry, the price determinants of small and family-owned hotels have not been addressed in research literature sufficiently. This research addresses those shortcomings and provides the basis for their future analysis. Furthermore, it explores the impact of two variables, which to our knowledge have not been discussed so far.
Keywords: 330; Small and family hotels; Price determinants; Hedonic pricing method; Southeastern/Mediterranean Europe